Perspectivas da utilização da tecnologia blockchain nos Correios - Carvalho, Joselma da Rocha (2018)
The main objective of this research was to investigate the possibility of use of blockchain technology by the Post Office, with a view to improving service delivery to the Brazilian population. The theoretical basis was based on a review of the literature on the term "Blockchain" in several journals, from which the articles of greatest relevance to the Postal Services were selected. The study was of the exploratory type and data collection was used through five methodologies: World Café, research questionnaire, literature review, unstructured interview and focus group. The research followed a qualitative approach, for the purpose of identifying business opportunities that can be generated in the postal service, from the adoption of blockchain technology. The study was carried out by the US POSTAL SERVICE (2016), which identified business opportunities and conveniences associated with the blockchain that could allow the expansion of postal services in the world. Thus, the present research sought to evaluate the possibilities of using the hypotheses raised in the services of the Correios do Brasil. Since it would not only allow these services to be conducted at a lower cost to the Post and its customers, but also to help the Post Office modernize and expand its operations. As results all the hypotheses raised were considered feasible by the respondents of the research questionnaire and legitimized by the articles researched in the literature review. Also proposed in the World Café, nine solutions for implementation of the blockchain in the Post Office. After being consolidated, these solutions were discussed by a focus group. Through the unstructured interview, we were able to promote the alignment of the study with the initiatives under development by the Government, validating the perception that blockchain technology can be an enabling tool, allowing the Postal Service to offer services more efficiently, swiftly, with lower cost and introducing a high level of automation to processes.